To assess the effectiveness of video-assisted teaching regarding the knowledge on prevention of ventilator-associated pneumonia in the intensive care unit among staff nurses of selected hospitals - Elsa Aniyan Samuel, Sherin; Karadkar, Gargee (International Journal of Nursing Research, 2023)
Introduction: Critically ill patients with respiratory failure, cardiac failure patients suffer from more serious illnesses. They are subjected to the invasive support and monitoring equipment. They require ventilator support for their life-saving. The mechanical ventilator will directly ventilate alveolar of lungs and increase the rate of depth breathing of the patients. VAP occurs as a result of a bacterial infection of the pulmonary parenchyma in mechanically ventilated patients due to aspiration, use of contaminated equipment, ingestion of contaminated medications, or colonization of the aero digestive tract. VAP is a major source of increased illness and death. Persons with VAP have increased lengths of ICU hospitalization and have up to a 20-30% death rate. Methodology: The research was conducted at two tertiary care hospitals (Karuna Hospital and Ashok Hospital, Borivali West) of the city (Mumbai) after obtaining the permission from the concerned authorities. In this study, it includes the staff nurses of the Intensive Care Unit of the selected hospitals. 120 Staff nurses of the Intensive Care Unit of the selected hospitals and 50 ICU Staff nurses were included. Data were collected according to the questionnaire. After collecting the Pre-test questionnaire, the investigator conducted a Video Assisted Teaching on prevention of VentilatorAssociated Pneumonia. On the seventh day, the post-test was done on the same samples by administering the same set of questionnaires. The questionnaires were completed in the presence of the investigator to avoid contamination, bias, and errors in the data collection. Results: Distribution of response in relation to the demographic variables revealed that the staff nurses 80% (20-30 yr), 18% (31-40 yr) , 2% (41-50 yr) .Most of the staff nurses, 72% were females and 28% were males and shows that there is no significant association of Gender on Mean knowledge Score during Post Test. Majority 52% were females and 12% males had qualification as GNM Nursing. 10% males and females had the qualification of BSc Nursing and 10% of females and 6% of males had the qualification of Post BSc Nursing. Most of the staff nurses, 52% were having 1-3 years of experience , 22% had 3.1 to 6 years of experience , 10% had 6.1 to 9 years of experience and 16% were above 9.1 years of experience and shows that there is no significant association of years of experience on Mean knowledge Score during post. The pre-test the mean of the knowledge obtained by the patient was 11.86 and in the posttest, it increased to 18. The ‘t’value was -8.19 and the ‘p’ value was 0.001(p < 0.05). Thus it is statistically interpreted that the Video Assisted teaching on prevention of Ventilator-Associated Pneumonia was effective. Hence the research hypothesis H1 was accepted. Conclusion: It was concluded that the video-assisted teaching on the prevention of ventilatorassociated pneumonia among the ICU staff nurses was found to be effective and also concluded undoubtedly that the videoassisted teaching prepared by the investigator helped the staff nurses to improve their knowledge about the prevention of ventilator-associated pneumonia.